PROGRAM KELURAHAN/DESA BERSIH NARKOBA (BERSINAR) OLEH BNN KOTA DUMAI TAHUN 2023 - Elviana, Elsa; ,, Hasanuddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Drug abuse and illicit trafficking pose a serious threat to national resilience, including in Dumai City, which geographically lies in a coastal area directly connected to international shipping routes in the Malacca Strait. This strategic position makes Dumai vulnerable to becoming an entry point for narcotics smuggling networks. Data from the National Narcotics Agency (BNN) indicates that Dumai ranked first for drug abuse cases in Riau Province in 2023, recording 117 cases with an increasing trend compared to the previous year. To address this issue, the Dumai City National Narcotics Agency (BNNK Dumai) implemented the Kelurahan Bersinar (Kelurahan Free from Drugs) program as a community-based prevention initiative at the local government level. This study aims to identify how the Kelurahan Bersinar program is implemented by BNNK Dumai and analyze the factors influencing its implementation. This research employed a qualitative descriptive approach, with data collected through interviews and documentation. Data were analyzed using data reduction, data display, and conclusion drawing techniques. The study applies Van Meter and Van Horn’s Policy Implementation Theory, which emphasizes six key variables: policy standards and objectives, resources, inter-organizational communication, characteristics of implementing agencies, socio-economic conditions, and implementers’ disposition. The results show that the implementation of the Kelurahan Bersinar program has been carried out through awareness campaigns, the establishment of community-based anti-drug activists, and coordination with related agencies. However, based on Van Meter and Van Horn’s theoretical analysis, several variables have not been optimally fulfilled, particularly those related to limited budget support, human resources, cross-sector coordination, and low community participation. These constraints contribute to the suboptimal implementation outcomes at the field level. Despite these challenges, the Kelurahan Bersinar program holds significant potential for strengthening community-based drug prevention efforts. Strengthening regulatory support, funding allocation, and multi- sector collaboration is required to ensure more effective and sustainable program implementation. Keywords: Bersinar Program, Drug Prevention, Dumai City National Narcotics Agency